Myocardial infarction causes inflammation and leukocyte recruitment at remote sites in the myocardium and in the renal glomerulus - Ruparelia, N; Digby, J; Jefferson, A; Medway, D; Neubauer, S; Lygate, C; Choudhury, R (2013)
Rationale and Objective Acute myocardial infarction (AMI) results in the recruitment of leukocytes to injured myocardium. Additionally, myocardium remote to the infarct zone also becomes inflamed and is associated with adverse left ventricular remodelling. Renal ischaemic syndromes have been associated with remote organ inflammation and impaired function. Here, we tested the hypothesis that AMI results in remote organ (renal) inflammation. Methods Mice were subjected to either AMI, sham procedure or no procedure and the inflammatory response in peripheral blood, injured and remote myocardium, and kidneys was studied at 24 h. Results AMI resulted in increased circulating neutrophils (P < 0.001) and monocytes (P < 0.001). mRNA for inflammatory mediators significantly increased in infarcted myocardium and in remote myocardium. VCAM-1 mRNA was increased in both infarcted and remote myocardium. VCAM-1 protein was also increased in the kidneys of AMI mice (P < 0.05) and immunofluorescence revealed localisation of VCAM-1 to glomeruli, associated with leukocyte infiltration and increased local inflammatory mRNA expression. Conclusions We conclude that in addition to local inflammation, AMI results in remote organ inflammation evidenced by (1) increased expression of mRNA for inflammatory cytokines, (2) marked upregulation of VCAM-1 in renal glomeruli, and (3) the recruitment and infiltration of leukocytes in the kidney. © The Author(s) 2013.